Kinetics of IL-6 production defines T effector cell responsiveness to regulatory T cells in multiple sclerosis - Trinschek, Bettina; Lüssi, Felix; Haas, Jürgen; Wildemann, Brigitte; Zipp, Frauke; Wiendl, Heinz; Becker, Christian; Jonuleit, Helmut (PLOS ONE, 2013)
In multiple sclerosis (MS) autoaggressive T effector cells (Teff) are not efficiently controlled by regulatory T cells (Treg) but the underlying mechanisms are incompletely understood. Proinflammatory cytokines are key factors facilitating Teff activity in chronic inflammation. Here we investigated the influence of IL-6 on Treg sensitivity of Teff from therapy-naïve MS patients with or without active disease. Compared to healthy volunteers and independent of disease course CD4+ and especially CD8+ MS-Teff were insensitive against functional active Treg from healthy controls. This unresponsiveness was caused by accelerated production of IL-6, elevated IL-6 receptor expression and phosphorylation of protein kinase B (PKB)/c-Akt in MS-Teff. In a positive feedback loop, IL-6 itself induced its accelerated synthesis and enhanced phosphorylation of PKB/c-Akt that finally mediated Treg resistance. Furthermore, accelerated IL-6 release especially by CD8+ Teff prevented control of surrounding Teff, described here as “bystander resistance”. Blockade of IL-6 receptor signaling or direct inhibition of PKB/c-Akt phosphorylation restored Treg responsiveness of Teff and prevented bystander resistance. In Teff of healthy controls (HC) exogenous IL-6 also changed the kinetics of IL-6 production and induced Treg unresponsiveness. This modulation was only transient in Teff from healthy volunteers, whereas accelerated IL-6 production in MS-Teff maintained also in absence of IL-6. Hence, we showed that the kinetics of IL-6 production instead of elevated IL-6 levels defines the Teff responsiveness in early Treg-T cell communication in MS independent of their disease course and propose IL-6 and associated PKB/c-Akt activation as effective therapeutic targets for modulation of Teff activity in MS.
Gesehen am 10.02.2022